2015
DOI: 10.1016/j.ijcard.2015.05.121
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between positive psychological constructs and health outcomes in patients with cardiovascular disease: A systematic review

Abstract: Depression and anxiety are well-known to be associated with adverse health outcomes in cardiac patients. However, there has been less work synthesizing the effects of positive psychological constructs (e.g., optimism) on health-related outcomes in cardiac patients. We completed a systematic review of prospective observational studies using established guidelines. A search of PubMed and PsycINFO databases from inception to January 2014 was used to identify articles. To be eligible, studies were required to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
101
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(113 citation statements)
references
References 82 publications
(124 reference statements)
9
101
0
3
Order By: Relevance
“…Across studies SWB and health and longevity are often, but not always related. For instance, DuBois et al (2015) reported that in 65% of the studies they reviewed a significant association was found after adjusting for one or more covariates. Thus, in about one-third of the studies a significant association was not found, and this raises the issue of moderation.…”
Section: Moderatorsmentioning
confidence: 99%
“…Across studies SWB and health and longevity are often, but not always related. For instance, DuBois et al (2015) reported that in 65% of the studies they reviewed a significant association was found after adjusting for one or more covariates. Thus, in about one-third of the studies a significant association was not found, and this raises the issue of moderation.…”
Section: Moderatorsmentioning
confidence: 99%
“…An emerging body of research has suggested that various facets of positive psychological well-being are associated with better health outcomes (3). In particular, dispositional optimismthe generalized expectation that good things will happenhas been linked with reduced risks of chronic health conditions, especially vascular factors and disease (3)(4)(5)(6)(7)(8)(9)(10). Importantly, although optimism is approximately 25% heritable (11), initial (albeit short-term) randomized trials have suggested that it can be modified using fairly accessible tools (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…However, research on optimism and long-term health to date is limited, with the most rigorous work primarily evaluating associations with cardiovascular morbidity and mortality (3)(4)(5)(6)(7)(8)(9)(10). A key question is whether optimism may be related to broader health outcomes.…”
mentioning
confidence: 99%
“…‱ Positive psychological variables Positive psychological well-being improves the outcome in terms of quality of life and disease management [133,134].…”
Section: Moderate Evidencementioning
confidence: 99%